Comparison of Validity of Mapping between Drug Indications and ICD-10 - Choi, Y.; Jung, C.; Chae, Y.; Kang, M.; Kim, J.; Joung, K.; Lim, J.; Cho, S.; Sung, S.; Lee, E.; Kim, S. (Methods of Information in Medicine, 2014)
Background: Mapping of drug indications to ICD-10 was undertaken in Korea by a public and a private institution for their own purposes. A different mapping approach was used by each institution, which presented a good opportunity to compare the validity of the two approaches.Objectives: This study was undertaken to compare the validity of a direct mapping approach and an indirect terminology based mapping approach of drug indications against the gold standard drawn from the results of the two mapping processes.Methods: Three hundred and seventy-five cardiovascular reference drugs were selected from all listed cardiovascular drugs for the study. In the direct approach, two experienced nurse coders mapped the free text indications directly to ICD-10. In the indirect terminology based approach, the indications were extracted and coded in the Korean Standard Terminology of Medicine. These terminology coded indications were then manually mapped to ICD-10. The results of the two approaches were compared to the gold standard. A kappa statistic was calculated to see the compatibility of both mapping approaches. Recall, precision and F1 score of each mapping approach were calculated and analyzed using a paired t-test.Results: The mean number of indications for the study drugs was 5.42. The mean number of ICD-10 codes that matched in direct approach was 46.32 and that of indirect terminology based approach was 56.94. The agreement of the mapping results between the two approaches were poor (kappa = 0.19). The indirect terminology based approach showed higher recall (86.78%) than direct approach (p < 0.001). However, there was no difference in precision and F1 score between the two approaches.Conclusions: Considering no differences in the F1 scores, both approaches may be used in practice for mapping drug indications to ICD-10. However, in terms of consistency, time and manpower, better results are expected from the indirect terminology based approach.
Keywords: Drug indication database; semantic mapping; International Classification of Diseases (ICD)